The Role of Foreign flow in Mediating the Influence of Firm Profitability, Firm Valuation, and Stock Liquidity on Stock Return - Hamdan, Ahmad Zulham; Indrawati, Nur Khusniyah; Champaca, Mychelia (JURNAL ILMIAH GEMA PERENCANA, 2025)
This study aims to examine and explain the influence of firm profitability, firm valuation, and stock liquidity on stock return, both directly and indirectly through foreign flow. This research is expected to enrich and complement the body of knowledge in the field of financial decision-making, particularly in signaling theory, and to provide valuable insights for both academics and practitioners. The population of this study consists of financial sector companies listed on the Indonesia Stock Exchange that reported positive profits and had foreign flow in their stocks during the period from 2022 to 2024. The sample for this study follows a census sampling method, where the entire population is selected as the sample. The total sample includes 77 financial companies over a three-year period, resulting in 231 observations for analysis. The analytical methods used are descriptive analysis and panel data regression with path analysis, utilizing STATA 17 software. The results indicate that stock liquidity and foreign flow have a significant effect on stock return, while firm profitability and firm valuation do not significantly impact stock return. Stock liquidity also significantly affects foreign flow, while firm profitability and firm valuation do not have a significant effect on foreign flow. Additional tests show that foreign flow has a mediating role in effect of firm valuation on stock return, but does not mediate the effect of firm profitability and stock liquidity on stock return.